(untitled) (Cadernos de Sociomuseologia, 2022)
Over the last decades of debate around archaeology of industrialization in Portugal, there has been a sample of examples in which different heritage perspectives have been discussed. We refer to cases that brought to the public space questions about the preservation, loss, reuse and even musealization of industrial spaces and contents. In this sense, we collected a sample of five examples that over the last 70 years generated more or less public debate around the industrial heritage. Most of the cases presented are all from the past 40 years, where the concepts of awareness and preservation of industrial heritage, although in permanent reflection and evolution, were already openly affirmed in the discussion. Different receptivity to these concerns, however, reflected different results. The main objective is to synthesize these different readings and sensitivities around the conservation and preservation of industrial heritage; simultaneously, we also tried to recover, from micromonographs, the memory (in some cases unpublished) of each of the cases in the sample. The survey and analysis of the cases were based on three methodological aspects: (1) historiographical and documental research; (2) on-site and remote sensing prospecting; (3) interaction of the two prospective bases in a documentary archaeology framework. Keywords: Industrial heritage; conservation criteria; public perception; documentary archaeology